Pelatihan Strategi Pemasaran dan Penjualan Berbasis E-Commerce pada Toko Sakura Kosmetik Sukoharjo - Purwanto, Eko; Utomo, Bangun Prajadi Cipto (Pakis Journal Institute, 2025)
This community service activity aims to implement marketing and sales strategies through the adoption of e-commerce at Sakura Kosmetik Store in Sukoharjo. The strategy is designed to market products more effectively via the internet by optimizing e-commerce applications. In this effort, the community service team implemented four main stages: (1) Preparation of marketing and sales management materials through e-commerce applications, (2) Partner training on e-commerce-based marketing strategies, (3) Partner assistance in applying the learned strategies, and (4) Continuous monitoring and evaluation to assess the impact of e-commerce implementation on marketing and sales management. The material preparation stage involves the creation of modules that include strategies for marketing and sales management through e-commerce, which are then used in training sessions. The training methods employed include discussions and demonstrations, focusing on easy-to-understand and applicable content for the partners. Monitoring is carried out periodically, starting with weekly evaluations to measure the progress of implementation, and continuing with long-term evaluations aimed at assessing the direct impact of e-commerce on the marketing and sales management performance at Sakura Kosmetik Store. The outcomes of this community service are expected to increase sales and improve the management of marketing and sales at the store.